Alteração de cor e sorção de resinas compostas imersas em água e soluções corantes - Laiber, Lara Paulino (2016)
The aim of this study was to evaluate the influence of distillate water and dark drinks storage on color stability and sorption of packable bulk fill composites of three different brands and to compare them with their corresponding conventional composites. 96 samples were prepared per type (bulk fill/conventional). Baseline color was measured according to the CIE L*a*b* system using a spectrophotometer. Specimens discs were randomly immersed for forty days in distilled water,coffee, red wine, and cola drink. Color difference (AE) was calculated based on the color coordinates before (baseline) and after staining treatment. The discs were weighed to assess sorption values. Then all samples were compared against each other. Data were analysed using2-way ANOVA and Duncan’s test (to compare all the groups and solutions) and Student test to intervals 10 and 40 days. FTKC group exhibited highest values for sorption in all the solutions, ARC was highest too for red wine and coke. ARBC showed highest AE values for water and coke. FTKC discs immersed in red wine exhibited highest AE values and both (ARBC and FTKC) showed high values in coffee. All the specimens were visually perceptible showing AE values higher than 3,3 over 40 days storage. AE values increased along the time for most of specimens and solutions.